Automated teller machine network market structure and cash usage - Heli Snellman (Bank of Finland, 2006)
This study discusses the effects of the Automated Teller Machine (ATM) network market structure on the availability of cash withdrawal ATM services and cash usage.The aim and novelty of the study is to construct the ATM equation.The study also contributes to the earlier discussion on the effects of ATMs on cash usage.The monopolisation of ATM network market structure and its effects on the number of ATMs and on cash in circulation are analysed both theoretically and empirically.The unique annual data set on 20 countries used in the estimations has been combined from various data sources.The observation period is 1988-2003, but the data on some countries are available only for a shorter period.Based on our theoretical discussion, as well as the estimation results, monopolisation of the ATM network market structure is associated with a smaller number of ATMs.Furthermore, the influence of the number of ATMs on cash in circulation is ambiguous.
URN:NBN:fi:bof-201408071675
Keywords: C33; E41; G2; C11; 330; ATM; ATM network; monopolisation; demand for cash; Electronic Banking; Zahlungsverkehr; Monopol; Geldnachfrage; Bargeld; OECD-Staaten